Self-assembly of the active lactone form of a camptothecin–phospholipid complex for sustained nuclear drug delivery. Issue 86 (7th September 2016) - Fan, Zhongxiong; Liu, Guihua; Li, Yang; Ma, Jinyuan; Lin, Jinyan; Guo, Fuqiang; Hou, Zhenqing; Xie, Liya
Abstract : (A) Illustration of the preparation of the CPT–SPC complex and its self-assembled nanoparticles (CPT–SPC NPs). (B) Illustration of drug delivery of the self-assembled CPT–SPC NPs. Abstract : 10-Hydroxycamptothecin (CPT) is considered as one of the most promising anticancer drugs against a broad spectrum of human cancers. However, it is difficult to apply CPT clinically, because of its poor water solubility and reversible instability between the active lactone and inactive carboxylate forms at neutral pH. In this paper, to overcome these limitations, the active lactone form of CPT–soybean phosphatidylcholine (SPC) complex self-assembled nanoparticles (CPT–SPC NPs) is prepared by a co-solvent method combined with a self-assembly technique. The CPT–SPC complex is characterized by solubility, UV-vis, 1 H NMR, FTIR, XRD, and fluorescence analysis. These results prove the efficient complexation between active lactone form of CPT and SPC (complexation rate was high as approximately 98%). The self-assembled CPT–SPC NPs show a hydrodynamic particle size of 210.7 ± 6.1 nm, a zeta potential of −24.9 ± 3.1 mV, a spherical shape, and a high drug-loading content of 16.3 ± 0.5%. CPT is released from the CPT–SPC NPs in a biphasic way with an initial burst release followed by a subsequent sustained release. Additionally, in comparision with the free CPT, the CPT–SPC NPs, because of the improved drug stability and enhanced drug transport across cellular membranes, present significantly higher cellular uptake efficiency and cell-killing effect of the drug. Moreover, both confocal imaging and fluorescence measurements demonstrate that CPT is able to be delivered to nuclei by the CPT–SPC NPs after their cellular uptake, by real-time monitoring of drug release and intracellular drug delivery. Furthermore, in vivo animal imaging results indicate that the systemically administered CPT–SPC NPs exhibit excellent tumor targetability in HeLa tumor-bearing nude mice. These results demonstrate that the CPT–SPC complex-based self-assembled NPs hold great potential as effective drug delivery systems for cancer treatment.